1994
DOI: 10.1080/00288306.1994.9514623
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic strain determinations from the Okarito and Godley‐Tekapo regions, central South Island, New Zealand

Abstract: This paper presents geodetic strain rate determinations from the Okarito area of South Westland aid the Godley Valley region in western Canterbury.In the Okarito area, the triangulation network extends from c. 10 km west of the Alpine Fault to 1 km east of the fault. To examine the distribution of strain about the fault, 1 broke the data into two subnetworks. One of the networks includes all stations located west of the Alpine Fault, and the other includes two stations located west of the fault and two station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…In each case the direction of horizontal principal contraction is within a few degrees of 110 ø, in good agreement with other measurements in the central South Island [Walcott, 1978[Walcott, , 1979Bibby et al, 1986;Reilly, 1990;Pearson, 1991Pearson, , 1994. Pearson [1994] showed that the 110 ø orientation is consistent with the Pacific-Australian plate motion predicted by the NUVEL-1 (and by implication the NUVEL-1A) plate velocity model. In order to better define the spatial distribution of strain, we magnitude and orientation of the axis of maximum relative contraction, together with its 95% confidence region.…”
Section: Results Of the Strain Determinationssupporting
confidence: 87%
“…In each case the direction of horizontal principal contraction is within a few degrees of 110 ø, in good agreement with other measurements in the central South Island [Walcott, 1978[Walcott, , 1979Bibby et al, 1986;Reilly, 1990;Pearson, 1991Pearson, , 1994. Pearson [1994] showed that the 110 ø orientation is consistent with the Pacific-Australian plate motion predicted by the NUVEL-1 (and by implication the NUVEL-1A) plate velocity model. In order to better define the spatial distribution of strain, we magnitude and orientation of the axis of maximum relative contraction, together with its 95% confidence region.…”
Section: Results Of the Strain Determinationssupporting
confidence: 87%
“…This direction is consistent within errors o: geodetically measured principal strains at 116° ± 14 in a survey network 30 km northeast of this study (Pearson 1994) Slickenside orientations on reverse faults in the duplex structures are oblique, with a mean rake of 55° (Fig. 7B) The shortening direction across the duplex can be estimated from the slickenside and fault orientations.…”
Section: Structural Summary and Interpretationsupporting
confidence: 87%
“…Seismicity and geodetie surveys confirm that deformation does currently occur east of the Alpine Fault (e.g., Rynn & Scholz 1978;Wood &. Blick 1986;Anderson & Webb 1994;Pearson 1994;Eberhart-Phillips 1995;Pearson et al 1995). However, offset marker horizons and datable surfaces are not common in the rapidly eroding and monotonous greywacke-schist sequences in the central Southern Alps.…”
Section: Geology Of Main Divide Regionmentioning
confidence: 99%
“…Late Quaternary strike-slip displacement rates along the Alpine Fault (27 ± 5 mm/yr) make up 70-75% of the fault-parallel interplate motion, and are relatively constant compared with dip-slip rates (0 to >10 mm/yr) which are greatest adjacent to the highest mountains (Norris & Cooper 2001). Geodetic surveys show that rocks in the immediate vicinity of the Alpine Fault are currently storing elastic strain energy that corresponds to 50-70% of the plate motion rate (Pearson 1994;Pearson et al 1995;Beavan et al 1999). …”
Section: Tectonic Settingmentioning
confidence: 99%